TWO NEW SPECIES OF STREPTOCARPUS (GESNERIACEAE) FROM TROPICAL AFRICA - Darbyshire, I.; Massingue, A. O. (Edinburgh Journal of Botany, 2014)
Two new species are described in the genus Streptocarpus (Gesneriaceae) from eastern tropical Africa. The first, Streptocarpus mazumbaiensis I.Darbysh. from the Usambara Mts of Tanzania, was treated as Streptocarpus sp. A in the Flora of Tropical East Africa account of the Gesneriaceae. The second, Streptocarpus acicularis I.Darbysh. & Massingue, is known from a single collection from the lower Chimanimani massif in Mozambique, previously misidentified as S. eylesii S.Moore. Both species are illustrated, their likely affinities are discussed and their conservation status is assessed.
Keywords: Chimanimani; conservation; Mozambique; Tanzania; taxonomy; Usambara